EFFECT OF ROUGHAGE TO CONCENTRATE RATIO ON QUALITATIVE AND QUANTITATIVE CHARACTERISTICS OF VEAL CARCASSES - Mahmood, Rabeea; Alrubeii, Amera; Alkudsi, Natik (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was conducted in the animal farm of the College of Agricultural Engineering Sciences/ University of Baghdad/ Iraq, from 23 march 2014 to 23 may 2014 to investigate the effect of two levels of roughage to concentrate ratio on qualitative and quantitative characteristics of Holstein Friesian veal’s, by studying the traits of three major muscles (longissimus dorsi LD, biceps femoris BF and semimembranosus SM). Two equal groups of Holstein Friesian veal’s were used. Each group was consilted of five veal’s at eight months old and weighted 228.800 ± 21.221Kg and 227.800 ± 9.167 Kg respectively. Lean chemical composition were studied with characteristics (pH, WHC, TVN, TBA, P.V, FFAs, myoglobin concentrations Mb and protein solubility PS). The results were confirming that a high effect of the diets contents on the muscles properties especially the fat contents. The muscle location had a strong effect too on muscle properties. LD muscle was in high difference always with the other two, in spite of the differences among all kinds of muscle in all traits.